2013
DOI: 10.2147/ijgm.s50134
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen potassium adenosine triphosphatase activity inhibition and downregulation of its expression by bioactive fraction DLBS2411 from Cinnamomum burmannii in gastric parietal cells

Abstract: This study assessed the gastric acid antisecretory effect of DLBS2411 fractionated from Cinnamomum burmannii. Hydrogen potassium adenosine triphosphatase (H+/K+ ATPase) activity and its gene expression were observed, and the antioxidant activity of DLBS2411 was also investigated. Treatment of DLBS2411 decreased the level of H+/K+ ATPase messenger RNA expression on human embryonic kidney 293 cells and rat gastric parietal cells in a dose-dependent manner, in vitro and ex vivo. DLBS2411 also acted as a competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Many of the nature-derived compounds have been directly utilized as drug entities; while many others can also serve as chemical models for the design, synthesis or semi-synthesis of novel drug molecules. A tremendous number of natural compounds are currently in various stages of clinical development, highlighting the significance and persisting viability of the nature-derived products as sources of new drug candidates [1][2][3][4][5][6][7][8]. This paper reviews Phyllanthus niruri L. (P. niruri), one herb species among the gigantic number of medicinal plants that have widely been studied worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the nature-derived compounds have been directly utilized as drug entities; while many others can also serve as chemical models for the design, synthesis or semi-synthesis of novel drug molecules. A tremendous number of natural compounds are currently in various stages of clinical development, highlighting the significance and persisting viability of the nature-derived products as sources of new drug candidates [1][2][3][4][5][6][7][8]. This paper reviews Phyllanthus niruri L. (P. niruri), one herb species among the gigantic number of medicinal plants that have widely been studied worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The results from both assays showed that DLBS2411 yielded free radical scavenging (antioxidant) activity that was lower than but comparable to ascorbic acid. 18 This antioxidant activity may also contribute to the gastroprotective effect yielded by DLBS2411 in this ethanol-induced gastric ulcer animal model.…”
Section: B a D C Ementioning
confidence: 92%
“…DLBS2411 was also reported to possess antioxidant activity and to show gastroprotective properties on acetic acid-induced gastric ulcer. 18,19 However, the effect of DLBS2411 on ethanolinduced gastric ulcer remains unclear. In this study, DLBS2411 was studied further in an animal model of gastric ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have conducted many studies on the potential use of herbal extracts for treatment of different kinds of diseases, especially on Cinnamomum burmannii extract for diabetes treatment. Combined with Lagerstroemia speciosa, C. burmannii has been found to induce insulin sensitivity in vitro as well as in patients in clinical studies (Nailufar and Tjandrawinata, 2011;Sitepu et al, 2016;Manaf et al, 2016;Kartolo et al, 2016;Tjandrawinata et al, 2013;Tandrasasmita et al, 2011;Tandrasasmita et al, 2014;Tjandrawinata et al, 2011). DLBS2411, a bioactive fraction containing C. burmannii, has previously been proven to affect hydrogen potassium adenosine triphosphate (H + /K + ATPase) activity as well as to down-regulate the gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…DLBS2411, a bioactive fraction containing C. burmannii, has previously been proven to affect hydrogen potassium adenosine triphosphate (H + /K + ATPase) activity as well as to down-regulate the gene expression. DLBS2411 was also reported to possess antioxidative activity (Tjandrawinata et al, 2013). Such pharmacological property would be beneficial for treatment and prevention of peptic ulcer.…”
Section: Introductionmentioning
confidence: 99%